2018
DOI: 10.1002/er.4343
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of various hybrid renewable energy systems using battery, hydrogen, and pumped hydro‐based storage units

Abstract: Summary The aim of this research is to analyze the techno‐economic performance of hybrid renewable energy system (HRES) using batteries, pumped hydro‐based, and hydrogen‐based storage units at Sharurah, Saudi Arabia. The simulations and optimization process are carried out for nine HRES scenarios to determine the optimum sizes of components for each scenario. The optimal sizing of components for each HRES scenario is determined based on the net present cost (NPC) optimization criterion. All of the nine optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 57 publications
(122 reference statements)
1
43
0
Order By: Relevance
“…It is well known that the metal dihydrides are attractive hydrogen storage materials because of their renewable, low cost, excellent deformation resistance, etc . Some noble metal hydrides have been investigated due to the good chemical stability and excellent catalytic activity . For example, the Pt‐Ru catalyst shows high hydrogen generation rate .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the metal dihydrides are attractive hydrogen storage materials because of their renewable, low cost, excellent deformation resistance, etc . Some noble metal hydrides have been investigated due to the good chemical stability and excellent catalytic activity . For example, the Pt‐Ru catalyst shows high hydrogen generation rate .…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Some noble metal hydrides have been investigated due to the good chemical stability and excellent catalytic activity. [16][17][18][19][20] For example, the Pt-Ru catalyst shows high hydrogen generation rate. 21 Ir-dopant can double enhance the hydrogen storage capacity of Pd nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have evaluated and demonstrated the cost-benefits of appropriate selection and application of different ESS technologies incorporation into the power system planning. The common ESS ranges from pumped hydro [20], hydrogen storage [21], BESS [22], compressed air energy storage, etc. [23].…”
Section: Introductionmentioning
confidence: 99%
“…1 However, renewable power generation, such as wind and PV power generation, will cause great disturbance to the power grid if connected to the grid directly, since it has the disadvantage of fluctuation and intermittence. 6,7 Pumped hydro storage (PHS) is a preferable storage device, with low cycle cost, and is considered the most mature technology. 4,5 Many storage devices have been applied in hybrid systems.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Many storage devices have been applied in hybrid systems. 6,7 Pumped hydro storage (PHS) is a preferable storage device, with low cycle cost, and is considered the most mature technology. 8 Several hybrid energy systems have been built in the world to date.…”
Section: Introductionmentioning
confidence: 99%